Nutritional quality, digestibility and growth performance of sheep fed fodder obtained from early-or-late-maturing groundnuts cultivars - Asare-Agyapong, E.; Abdul Rahman, Nurudeen; Addah, W.; Ayantunde, Augustine A. (University for Development Studies, 2021)
This study determined the digestibility and growth performance of sheep fed groundnut fodder obtained from early- or late-maturing cultivars. Early-maturing cultivars (90 days) included Chinese, Yenyawoso and Sumnut 23 whereas late-maturing cultivars (110 to 120 days) were Sumnut 22, Azivivi and Manipinta. Each variety was cultivated on 4 replicated fields. At maturity, all the cultivars were harvested. The pods were separated from the haulms (leaves and twigs) and equal portions of the haulms were composited into early- or late-maturing cultivars. Each of the composited haulms was then dried and chopped to a theoretical length of 3–4 cm before being used to formulate two diets that were fed to twenty-two West African Dwarf sheep (14.75±2.52 kg) in a 45-d feeding trial. Two ruminally-cannulated Nungua Black Head sheep were used to determine the digestion kinetics of the fodder in an in situ digestibility experiment whereas in vitro digestibility of the fodder at 48 h was also assessed. The early-maturing cultivars had higher concentrations of acid detergent fibre (ADF; P = 0.01) and acid detergent lignin (ADL; P = 0.02) but lower (P = 0.02) concentration of dry matter (92.4 vs. 93.3%) compared to the late-maturing cultivars. The concentration of silica differed between the two cultivars by 44%, as it tended (P = 0.08) to be higher in the late-maturing compared to the early- maturing cultivars (2.6 vs. 1.8%). The higher concentrations of ADF and ADL in the early-maturing cultivars reduced (P = 0.03) the extent of digestion of this fodder compared to the late-maturing cultivars (43.9 vs. 52.1% DM). Growth performance of sheep fed the groundnut fodder did not differ statistically (P ≥ 0.69). This study concludes that late-maturing cultivars produced more DM and had less recalcitrant fibre constituents (ADF and ADL) than early-maturing cultivars. Improvements in the extent of digestion of the late-maturing groundnut cultivars did not reflect in the growth performance of sheep fed the late-maturing groundnut fodder.